The Role of Binders for Water-Based Anode Dispersions in Inkjet Printing - Cara Greta Kolb; Alessandro Sommer; Maja Lehmann; Carys-May Teixeira; Hannes Panzer; Saeed Maleksaeedi; Michael Friedrich Zaeh (Batteries, 2023)
Binders play a pivotal role in the production and the operation of lithium-ion batteries. They influence a number of key dispersion characteristics and battery parameters. In the light of growing interest in additive manufacturing technologies, binders were found to decisively govern the processability due to the induced complex non-Newtonian behavior. This paper examines the relevance of various binder derivatives for aqueous graphite dispersions that can be employed in inkjet printing. Two different carboxymethyl cellulose (CMC) derivatives with strongly deviating molecular weights were employed. The impact of the inherent polymer characteristics on the processability and the electrode characteristics were explored. Therefore, miscellaneous studies were carried out at the dispersion, the electrode, and the cell levels. The results revealed that the CMC with the lower molecular weight affected most of the studied characteristics more favorably than the counterpart with a higher molecular weight. In particular, the processability, encompassing drop formation and drop deposition, the cohesion behavior, and the electrochemical characteristics, were positively impacted by the low-molecular-weight CMC. The adhesion behavior was enhanced using the high-molecular-weight CMC. This demonstrates that the selection of a suitable binder derivative merits close attention.